2016
DOI: 10.1111/cen.13053
|View full text |Cite
|
Sign up to set email alerts
|

Can the follow‐up of patients with papillary thyroid carcinoma of low and intermediate risk and excellent response to initial therapy be simplified using second‐generation thyroglobulin assays?

Abstract: Our results confirm that in patients with PTC of low or intermediate risk an excellent response to initial therapy can be defined based on nonstimulated Tg ≤ 0·2 ng/ml. Follow-up consisting only of clinical examination and periodic measurement of Tg with a second-generation assay may be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Several studies have shown that undetectable post-operative Tg levels correspond with a low incidence of recurrence, while elevated Tg levels are associated with recurrence (1215). Rosario and colleagues demonstrated that Tg levels often detected recurrent PTC, even prior to structurally detectable disease on ultrasound (16). One study evaluating the risk of recurrent PTC demonstrated an increase in Tg more than 2 fold was seen in 80% of patients with recurrence and only 13% of patients without recurrent PTC (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that undetectable post-operative Tg levels correspond with a low incidence of recurrence, while elevated Tg levels are associated with recurrence (1215). Rosario and colleagues demonstrated that Tg levels often detected recurrent PTC, even prior to structurally detectable disease on ultrasound (16). One study evaluating the risk of recurrent PTC demonstrated an increase in Tg more than 2 fold was seen in 80% of patients with recurrence and only 13% of patients without recurrent PTC (17).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of highly sensitive Tg (hsTg), whose functional sensitivity is about 0.1 or 0.2 ng/mL, allows for the simplification of the follow-up protocol, avoiding the need for stimulated Tg (stTg). In fact, hsTg proved its equivalence in revealing distant metastases compared with stTg, even in patients without RRA [ 32 , 33 , 34 , 35 ].…”
Section: Radioiodine Treatment Goalsmentioning
confidence: 99%
“…On the other hand, radioisotopes (RI) have emerged as power radio-therapeutic agents and have been widely utilized in clinical practices. Radionuclide such as isotope [ 89 Sr] has been employed for metastatic bone cancers 5 and isotope [ 131 I] is used as radio-therapeutic medicine for thyroid cancers 6 . More importantly, radiolabeled biomolecules have become more useful as tumor-targeting drugs for specific radiations.…”
Section: Introductionmentioning
confidence: 99%